Borrmann Type 4 Advanced Gastric Cancer: Focus on the Development of Scirrhous Gastric Cancer - Kyoungwon Jung; Moo In Park; Sung Eun Kim; Seun Ja Park (Korean Society of Gastrointestinal Endoscopy, 2016)
Early diagnosis of Borrmann type 4 advanced gastric cancer (AGC) is very important for improving the prognosis of AGC patients. Because there is no definite mass in most cases of Borrmann type 4 AGC, its accurate diagnosis via endoscopy requires an understanding of its pathogenesis and developmental process. Moreover, many people confuse linitis plastica (LP) type gastric cancer (GC), scirrhous GC, and Borrmann type 4 AGC. To distinguish each of these cancers, knowledge of their endoscopic and pathological differences is necessary, especially for LP type GCs in the developmental stage. In conclusion, diagnosis of pre-stage or latent LP type GC before progression to typical LP type GC requires the detection of IIc-like lesions in the fundic gland area. It is also crucial to identify any abnormalities such as sclerosis of the gastric wall and hypertrophy of the mucosal folds during endoscopy.